Flexible ferroelectric element based on van der Waals heteroepitaxy - Jiang, Jie (Sci Adv, 2017)
We present a promising technology for nonvolatile flexible electronic devices: A direct fabrication of epitaxial lead zirconium titanate (PZT) on flexible mica substrate via van der Waals epitaxy. These single-crystalline flexible ferroelectric PZT films not only retain their performance, reliability, and thermal stability comparable to those on rigid counterparts in tests of nonvolatile memory elements but also exhibit remarkable mechanical properties with robust operation in bent states (bending radii down to 2.5 mm) and cycling tests (1000 times). This study marks the technological advancement toward realizing much-awaited flexible yet single-crystalline nonvolatile electronic devices for the design and development of flexible, lightweight, and next-generation smart devices with potential applications in electronics, robotics, automotive, health care, industrial, and military systems.